Agarofuran sesquiterpenes from Schaefferia argentinensis - García, Manuela Emila (2013)
Sixteen dihydro-β-agarofuran sesquiterpenes were isolated from the aerial parts of Schaefferia argentinensis Speg. Their structures were determined by a combination of 1D and 2D NMR and MS techniques. The in vitro antiproliferative activity of the major sesquiterpenes was examined in T47D, MCF7, and MDA-MB231 human cancer cell lines, but was found to be marginal.